Antimicrobial Activity of Medicinal Plants Correlates with the Proportion of Antagonistic Endophytes - Egamberdieva, Dilfuza; Wirth, Stephan; Behrendt, Undine; Ahmad, Parvaiz; Berg, Gabriele (Frontiers in Microbiology, 2017)
Medicinal plants are known to harbor potential endophytic microbes, due to their bioactive compounds. In a first study of ongoing research, endophytic bacteria were isolated from two medicinal plants, Hupericum perforatum and Ziziphora capitata with contrasting antimicrobial activities from the Chatkal Biosphere Reserve of Uzbekistan, and their plant-specific traits involved in biocontrol and plant growth promotion were evaluated. Plant extracts of H. perforatum exhibited a remarkable activity against bacterial and fungal pathogens, whereas extracts of Z. capitata did not exhibit any potential antimicrobial activity. Matrix-assisted laser desorption ionization (MALDI) time-of-flight (TOF) mass spectrometry (MS) was used to identify plant associated culturable endophytic bacteria. The isolated culturable endophytes associated with H. perforatum belong to eight genera (Arthrobacter, Achromobacter, Bacillus, Enterobacter, Erwinia, Pseudomonas, Pantoea, Serratia and Stenotrophomonas). The endophytic isolates from Z. capitata also contain those genera except Arthrobacter, Serratia and Stenotrophomonas. H. perforatum with antibacterial activity supported more bacteria with antagonistic activity, as compared to Z. capitata. The antagonistic isolates were able to control tomato root rot caused by F. oxysporum and stimulated plant growth under greenhouse conditions and could thus be a cost-effective source for agro-based biological control agents.